Effectiveness of assertive case management for patients with suicidal intent. (October 2021) - Inui-Yukawa, Masami; Miyaoka, Hitoshi; Yamamoto, Kenji; Kamijo, Yoshito; Takai, Michiko; Yonemoto, Naohiro; Kawanishi, Chiaki; Otsuka, Kotaro; Tachikawa, Hirokazu; Hirayasu, Yoshio
Highlights: Assertive case management decreased suicide attempts in self-poisoning patients. Assertive case management reduced repeated self-harm in self-poisoning patients. Assertive case management was especially effective for self-poisoning patients. Abstract: The aim of this study was to examine the effectiveness of assertive case management intervention in preventing suicidal behaviour in self-poisoning patients. We conducted a secondary analysis of data from the ACTION-J study. Participants were self-poisoning patients with clear suicide intent admitted to emergency departments and with a primary psychiatric diagnosis (as per DSM-IV-TR axis 1). Patients were randomly assigned either to assertive case management or enhanced usual care. The primary outcome measure was the incidence of a first recurrent suicide attempt within 6 months. This study is registered at ClinicalTrials.gov (NCT00736918) and UMIN-CTR (C000000444). There were 297 self-poisoning patients in the intervention group and 295 in the control group. The primary outcome was significantly lower in the intervention group than in the control group. The incidence of a first recurrent suicide attempt within 1 and 3 months was also significantly lower in the intervention group, as was the number of overall self-harm episodes over the entire study period. Furthermore, the number of non-suicidal self-harm episodes and suicide attempts was significantly lower in the intervention group. Assertive case management is effective when promptly introduced in a hospital setting as an intervention following a suicide attempt, particularly for self-poisoning patients.